Percepção dos alunos sobre serpentes em uma escola pública no sudoeste do Amazonas - Souza, Izabela Augusta Veiga de (Brasil, 2019)
It is believed that snakes appeared approximately 140 million years ago. And knowing them is of fundamental importance. Therefore, this work aims to verify the students' perception about snakes in a public school in the municipality of Humaitá-AM. The research took place in the first semester of 2019, in the Municipal School Center of Excellence Sister Carmem Cronenbold, contemplating students of the 7th year of elementary school in the morning shift. An unstructured questionnaire was applied in order to know the previous knowledge that the students had about snakes. It has been found that students have significant knowledge about snakes and are afraid to spot them. Most of the students mentioned that they know people who have had snake-related accidents and that they should have hospital treatment as soon as possible. Therefore, the research carried out showed that the students present significant knowledge regarding amphibians and reptiles, although there is confusion in correctly identifying the two groups of animals mentioned here.